Kemampuan implementasi kebijakan desentralisasi dan otonomi daerah :: Studi kasus Kabupaten Dati II Banyumas - RUDWIANTO, Didi (Universitas Gadjah Mada, 1998)
An issue about the local autonomy as the manifestation of decentralized policy has always been the main topic of discussion, either among the exprts, the bureaucrat elites, or the implementor at a central and a local government, press and mass media which comes up more massivelly to the surface at recent time after a policy of local autonomy pilot project was implemented in 26 sample on the second stage local (Daerah Tingkat //). The matters is easily understood, as for 23 years the local autonomy and decentalized policy stated on A d No. 5 of 1974 on the Principles of Administration in Indonesian Local Government and is even followed by PP No. 45 of 7992 and PP No. 8 of 7995 as an operational elaboration to emphasize on a local autonomy on the second stage local, yet its implementation is experiencing some hindeaces and for away from the ideal, it is even tends to centralistic government The direct implementation of decentralized policy and local autonomy will involve intendion between central government and the first stage of local government (&ti I), central government and the second of local government (Dafj /I), and interaction between the first stage of local and the second stage of local government. In which the interaction of the those government are indicated by inducement and contrain factors influencing the ability of region in implementing the policy, both factors, then cuuse trade off between the implementation of local autonomy and decentralbation, in one side, and the control of central government, on the other side. Based on the result of research using policy implementation approach at the implementation of decentralized and local autonomy policy in Kabupaten Dati II Banyumas, the writer found the description of the interaction between central bureaucrats and local bureaucrats indicated by trade off proses (inducement and contrain) at the direct implementation. That matter is indicated by unclarity of affair delegating implementation mechanism which is not in line wiht available finance, personal and equipment, so that it cause the second stage local in hard position, even the afffairs delegated do not give positive impacts to the increasing local income (PADS) for ttre potential resources are not delegated on the contrary they are recentralised. The condition indicates the existence of great power and authority at central government and the first stage of local, which cause level of dependency Pemda Tk I / Banyumas to the Pemda Tk / Jawa Tengah and central governments authority is still powerful and make the dependency of Dati 1 1 Banyumas is getting weaker in managing government and local development. That is why it is needed to have the same vision, perception and a good will of the government implementation either of central or local government in achieving decentralized implementaion and local autonomy policy which is more consistent While an effort to incrase the ability of Dafi / I Banyumas in implementing decentralized and local government policy needs discreation to make improvisation by using natural, local finance, and optimal human resources.